Cost analysis of oral antihypertensive drugs available in the retail pharmacies in Bhairahawa, Nepal - Kandel, K; Karki, N; Paudel, S; Shresth, L; Yadav, NK (Devdaha Medical Journal, 2025)
Introduction: Hypertension is highly prevalent in Nepal, but its treatment and control are poor due to high drug costs and weak regulation. Most patients have to pay on their own, hence the variations in prices of antihypertensive drugs increase financial burden, limiting effective management. The purpose of this study was to analyze the variation in price of different brands of same oral antihypertensive agent available in the retail pharmacies located in Bhairahawa and to compare the cost of antihypertensive agents manufactured by Nepalese and Indian pharmaceutical industries. Methods: A cross-sectional descriptive study was conducted at the randomly selected 42 registered retail pharmacies located in Bhairahawa Nepal over one year period for cost analysis of oral antihypertensive agents. Results: Cost variation was observed in 14 different formulations of oral antihypertensive agents (87.5%) out of 16 different formulations analyzed. The maximum cost variation (CV) among individual preparations was observed with S (-) Amlodipine 5mg tablet (%CV: 116.43%) whereas among combination preparations, maximum price variation was observed with Furosemide 20mg + Spironolactone 50mg tablet (%CV: 138.13%). The Result of Two-Sample t-test showed no significant mean difference between price of Nepalese and Indian brands of antihypertensive drugs. Conclusion: There is significant variation in the price of oral antihypertensive agents available in the retail pharmacies in Bhairahawa. Such price variation can act as a barrier in the treatment and control of hypertension especially when physicians prescribe a more expensive brand. Thus, it is highly necessary for government and other concerned authorities to develop and implement better pricing strategies.